Internet safety: Teaching children to keep themselves safe. (2nd December 2020) - Lepkowska, Dorothy
Abstract : Dorothy Lepkowska discusses tips for teaching children how to use the internet safely and judge the information available to them, which comes after the announcement that millions of children will once again be taught remotely during lockdown.